Synthesis and Spectral Studies on Co2+, Ni2+ and Fe2+, Complexes with o-, p-, m-methoxyphenylimino-1-phenyl-2-hydroxyiminopropane - Rai, H.C.; Kumari, Vibha (Asian Journal of Chemistry, 2010)
A series of CO2+, Ni2+, and Fe2+ complexes of the type M(HL1,2,3)2X2, where M=Co(II), Ni(II) and Fe(II); HL1, HL2, HL3= 1-o-, p-, m-methoxyphenylimino-1-phenyl-2-hydroxyiminopropane have been synthesized and characterized by analytical, conductivity, thermal and magnetic, infrared and electronic spectral data. The studies show that the complexes are isostructural and possess octahedral geometry. Semi-quantitative group theoretical study suggests complexes to possess trans- structure.